Walkers and their Staffs: O'odham Walking Sticks by Way of Calendar Sticks and Scraping Sticks. (27th October 2016) - Schermerhorn, Seth
Abstract: As archaeologist J. Andrew Darling and Akimel O'odham traditional singer and cultural preservation officer Barnaby V. Lewis have previously shown, scraping sticks encode geographical knowledge, while calendar sticks encode historical knowledge. Like these other sticks, the staffs of O'odham "walkers, " or pilgrims, to Magdalena, Sonora, Mexico, similarly contain both geographical and historical knowledge, evoking memories of past journeys in the present and the presence of Magdalena. Moreover, these staffs are spoken of and treated as people, or at least as an extension of O'odham walkers. For O'odham walkers with their staffs, or walking sticks, Magdalena, Saint Francis, and all of the blessings associated with them are never too far away. And the memories of these journeys that they have taken with their sticks and the stories that they together tell, inextricably link walkers and their sticks, sticks and stories, people and places, as well as the past and the present. Thus, Magdalena is palpably present in the everyday lives of the walkers who cannot help but be transported by their sticks to stories—whether told or untold—and memories made along the road to Magdalena as well as dreams of future journeys.